Cholecystokinin bioactivity in human plasma. Molecular forms, responses to feeding, and relationship to gallbladder contraction. - Liddle, R A (1985)
A sensitive and specific bioassay for the measurement of cholecystokinin (CCK) in human plasma was developed to determine the molecular forms of CCK in circulation, CCK responses to feeding, and the physiologic role of CCK in gallbladder contraction. First, plasma was quantitatively extracted and concentrated with octadecylsilylsilica, and the extracts were then assayed for their ability to stimulate amylase release from isolated rat pancreatic acini. Acini were highly sensitive to CCK whereas gastrin reacted only weakly in this system. With the assay, plasma levels of cholecystokinin octapeptide (CCK-8) bioactivity as low as 0.2 pM were detectable. CCK bioactivity in plasma was inhibited by the CCK antagonist, bibutyryl cyclic guanosine monophosphate, and was eliminated by immunoadsorption with an antibody directed against the carboxyl terminus of CCK. Detection of fasting levels of CCK was possible in all individuals tested and averaged 1.0 +/- 0.2 pM (mean +/- SE, n = 22) CCK-8 equivalents. Plasma CCK biological activity was normal in patients with gastrin-secreting tumors. After being fed a mixed liquid meal, CCK levels rose within 15 min to 6.0 +/- 1.6 pM. The individual food components fat, protein, and amino acids were all potent stimulants of CCK secretion; in contrast, glucose caused a significant but smaller elevation in plasma CCK levels. Gel filtration studies identified three major forms of CCK bioactivity in human plasma: an abundant form that eluted with CCK-33, a smaller form that eluted with CCK-8, and an intermediate form that eluted between CCK-33 and CCK-8. Ultrasonic measurements of gallbladder volume indicated that this organ decreased 51% in size 30 min after feeding a mixed liquid meal. This contraction occurred coincidentally with the increase in plasma CCK levels. Next CCK-8 was infused to obtain CCK levels similar to postprandial levels. This infusion caused a decrease in gallbladder volume, similar to that seen with a meal. The present studies indicate, therefore, that CCK can be bioassayed in fasting and postprandial human plasma. These studies also suggest that CCK may be an important regulator of gallbladder contraction.